Effects of Xylanase and Bacterial Inoculants on In Vitro Rumen Fermentation Pattern of Seasonal Pasture Hay and Green Maize Based Silage - Kansagara, Yash G.; Savsani, Harish H.; Chavda, Mitesh R.; Chavda, Jignesh A.; Makwana, Rinkesh B.; Karangiya, Vijay K.; Belim, Saman Y.; Makwana , Kirti R. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to evaluate the effects of xylanase and bacterial inoculants on in vitro rumen fermentation pattern of seasonal pasture hay and green maize based silage. Different silages were prepared by using green maize fodder and seasonal pasture hay in the proportion of 10:0 & 7:3 ratio in plastic jars of 3 kg capacity by adding common salt @ 0.5%, urea @ 1% and molasses @ 1.5% in each silage with seven different treatments, viz., Control (only green maize), PH (green maize and seasonal pasture hay in 7:3 ratio), X (PH added with xylanase), LP (PH added with  L. plantarum), LF (PH added with L. fermentum), LPLF (PH added with both bacterial inoculants) and XLPLF (PH added with xylanase and both bacterial inoculants). Xylanase, L. plantarum and L. fermentum were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were used for in vitro study after 45 days of ensiling. None of the additives affected rumen pH. IVDMD  (in vitro dry matter degradability ) was found significantly (p
Keywords: Bacterial inoculants; Green maize; Seasonal pasture hay; Silage; Xylanase